A Note on the Stefan-Boltzmann Problem for Heat Transfer in a Fin (Journal of Nonlinear Modeling and Analysis, 2024)
A fin is traditionally thought of as an extension of a surface tofacilitate the transfer of heat away from a larger body to which it is attached.In this paper, the authors study some mathematical properties of a nonlinearheat transfer model for a fin and its relation to an associated linear model.Specifically, they prove that the solution exists and is unique, and they determine bounds for the temperature. Further, they prove the monotonicityof the temperature distribution, and they obtain an estimate for the maximaldifference between the temperatures as determined by the nonlinear and linearmodels.